Lost and Found in Translating Tourist Texts Domesticating, Foreignising or Neutralising Approach - He Sanning (JoSTrans: The Journal of Specialised Translation)
Domesticating and foreignising strategies are popular in translation studies and each of them has its own advantages and disadvantages in translating tourist texts. The advantages for domesticating include maintaining the terseness of the text, obtaining the reader’s understanding of the translated text, and gaining the interest of the reader. Its biggest weakness is that the cultural and historical elements of the original could be lost in translation. The advantages for foreignising are revealing the cultural and historical factors of the Source Text (ST), and disseminating the culture and customs of the original. Its disadvantages are neglecting the reader’s understanding, and the function of attracting the tourists may be lost. This paper argues that neither of them can solve all the problems associated with translating tourist texts from Chinese to English. The major focus of this paper is to find a new translation strategy that can highlight and introduce Chinese culture to the target audience and keep Chinese culture intact. This neutralising strategy with its information-oriented, association-applied and concept-based principles can be employed to ensure the equivalents in information, concept and aesthetics.